Trade union defense of public space: The Case of Haydarpaşa Railway Station - Tolga Tören (Global Labour University - Freunde und Förderer e.V., 2024)
Since the beginnings of the 2000s, but especially in the aftermath of the 2008 crisis in Turkey, many policy texts as well as publications expressing the expectations of the business community began to emphasise the importance of the transport sector for the Turkish economy, based on the claim that the country's transport infrastructure should be built in such a way as to connect production centres with the market at the highest possible speed and at the lowest possible cost. During this period, many infrastructure investments in the form of public-private partnership projects (PPP) in many areas of the transport sector, especially motorways and airports, came to the fore in Turkey, and some strategically important ports, roads or railway institutions began to be subjected to privatisation, commercialisation and deregulation. Another dimension of the process mentioned above is the projects that aim not only to make large investments in transport, called "megaprojects", but also to articulate public urban spaces to these megaprojects by commodifying these spaces through the creation of new rental areas, as in the case of the Haydarpaşa Railway Station, which was opened in 1872 in İstanbul's Asian-side district of Kadıköy beside the Bosphorus with the idea that the freight carried by trains reaching the station could be transferred to the ships in the Bosphorus (Fuhrmann, 2022; Middleton, 2011; Wikipedia, 2023a). In 2004, the Justice and Development Party (AKP) government included the station and a million square metre area of the port next to the station in the urban transformation project, which included many examples of gentrification, such as turning the area into a gallery of shopping malls, luxury hotels, luxury apartments and marinas. The project had a complementary relationship with another project, the Marmaray Tube, which connects the Anatolian and European sides of İstanbul with a tube under the Marmara Sea. This means that the Marmaray Tube allows passengers travelling to İstanbul by train from Anatolian cities, or by suburban train from districts on the Anatolian side of İstanbul, to bypass the Haydarpaşa station and travel to the European side through a tunnel under the Marmara Sea. Once the Marmaray Tube is launched, passengers using rail transport would be able to cross to the European side through the Marmaray Tube instead of the ferries that leave Haydarpaşa and reach the opposite shore in about 15 minutes (Fuhrmann, 2022). Therefore, the restructuring of Haydarpaşa station and its surroundings as a rent-seeking area and the Marmaray Tube project were closely linked. In fact, Haydarpaşa station was closed to train traffic after the Marmaray Tube was inaugurated in 2013. (...)
Keywords: 330